Property prices and Covid-19 related administrative closures: What are the implications? - Matthew Allen-Coghlan; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2020)
In this paper we examine the implications for the Irish housing market of the economic slowdown due to the Covid-19 virus. While necessary from a public health perspective, the administrative closure implemented by the Irish authorities in March 2020 has had several significant repercussions for the domestic residential market. As hundreds of thousands of workers lose their jobs over a short period of time, income levels in general are set to fall across the economy, with knock-on implications for affordability and housing demand. Additionally, the nature of the administrative closedown will also impact the residential market through the collapse in housing related activity for the period in question. In this paper we augment an inverted demand function for housing to include a residential market activity variable and estimate the impact on house prices of the decline in economic activity due to the virus-related measures. We also examine the likely future path of house prices based on two different recovery scenarios with a series of house price forecasts to the end of 2021.
Keywords: E31; G12; E60; 330; House prices; Covid-19; Mortgages